2003
DOI: 10.1097/00006254-200302000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: After completion of this article, the reader will be able to list the various ocular changes that occur during pregnancy, summarize the ocular disturbances that occur with preeclampsia and diabetes, and describe the management of some ocular problems during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Visual acuity disturbances are common complaints in pregnancy suggesting the presence of underlying diseases including diabetes, preeclampsia, or refractive eye disorders [ 1 – 3 ]. However, most cases are just related to physiology of pregnancy and hence do not need serious medical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visual acuity disturbances are common complaints in pregnancy suggesting the presence of underlying diseases including diabetes, preeclampsia, or refractive eye disorders [ 1 – 3 ]. However, most cases are just related to physiology of pregnancy and hence do not need serious medical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exudative retinal detachment is seen in 1% of preeclamptic patients and 10% of eclamptic patients 36. In a Turkish study by one of the authors of this manuscript (RBK) including 47 patients with preeclampsia, 3 patients exhibited exudative retinal detachment; two of the cases resolved spontaneously following birth, while one required postpartum systemic steroid treatment due to very low visual acuity.…”
Section: Pathological Ocular Changesmentioning
confidence: 84%
“…36 Although the standard treatment is oral steroids, posterior sub-Tenon’s triamcinolone injection is recommended for pregnant patients. 12 …”
Section: Pathological Ocular Changesmentioning
confidence: 99%
“…The macula is especially affected by pregnancy even when healthy – for example, two studies reported infrequent central serous chorioretinopathy in the third trimester in healthy pregnant women 7,8. Complications of pregnancy, especially preeclampsia, can lead to loss of vision but these often subside postpartum 9,10…”
Section: Discussionmentioning
confidence: 99%